Knowledge, Personal Hygiene and The Incidence of Hepatitis A in Students of University of Jember - Septivita, Dian; Ma’rufi, Isa; Ningtyias, Farida Wahyu (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-